Correlates of intimate partner violence against women during a time of rapid social transition in Rwanda: analysis of the 2005 and 2010 demographic and health surveys - Thomson, Dana R. (BMC Womens Health, 2015)
BACKGROUND: In Rwanda, women who self-reported in household surveys ever experiencing intimate partner violence (IPV) increased from 34 % in 2005 to 56 % in 2010. This coincided with a new constitution and majority-female elected parliament in 2003, and 2008 legislation protecting against gender-based violence. The increase in self-reported IPV may reflect improved social power for women, and/or disruptions to traditional gender roles that increased actual IPV. METHODS: This is a cross-sectional study of IPV in 4338 couples interviewed in the 2005 and 2010 Rwanda Demographic and Health Surveys (RDHSs). Factors associated with physical or sexual IPV in the last 12 months were modeled using manual backward stepwise logistic regression. Analyses were conducted in Stata v13 adjusting for complex survey design. RESULTS: Risk factors for IPV in 2005 (p < 0.05) were: experiencing emotional IPV (OR = 18.1), beating husband/partner unprovoked (OR = 12.3), witnessing IPV against mother (OR = 1.82), husband/partner consumes alcohol often (OR = 3.13), and polygynous marriage (OR = 1.51), whereas having a husband/partner with secondary education (OR = 0.43) was protective. Factors associated with increased IPV in 2010 (p < 0.05) were husband/partner (OR = 1.30) or woman (OR = 1.36) believes IPV is justified, husband/partner has sex with non-marital partners (OR = 2.52), bottom wealth quintile (OR = 1.25), polygynous marriage (OR = 2.29), having a son (OR = 2.05) or only daughters (OR = 2.58) versus no children, and having a husband/partner employed with in-kind versus cash compensation (OR = 1.58). In 2010, woman being involved with her own health (OR = 0.79) or earnings (OR = 0.57) decision-making was protective against IPV. Several variables were not available in the 2010 RDHS. CONCLUSIONS: Our results may provide evidence of both increased self-reporting of IPV and social power disruption. Rwanda’s Isange One Stop Center project, with medical, legal, and psychosocial services for domestic violence victims, is currently scaling to all 44 district hospitals, and police station gender desks reduce barriers to legal reporting of IPV. Additional support to Abunzi mediators to hear IPV cases in communities, and involvement of men in grassroots efforts to redefine masculinity in Rwanda are suggested. Additional research is needed to understand why self-reported IPV has increased in Rwanda, and to evaluate effectiveness of IPV interventions.